Employee Engagement Comparative Study of Baby Boomers, x, and y Generation Workers in Transportation and Logistics Delivery service Companies Semarang - Kurniawati, Nurul Imani (Universitas Diponegoro, 2022)
Studies related to workers across generations have caught the attention of many researchers. For the first time in history, the company is inhabited by workers from various generations to be able to work side by side. How workers in each generation interact with and influence the organization they work for is still an interesting research gap to study. However, the studies examining employee engagement in the Baby Boomers generation, X generation and Y generation in transportation companies and logistics delivery services are still limited. Therefore, this study aims to conduct research on the differences in employee engagement in the Baby Boomers generation, X generation and Y generation in transportation and logistics delivery service companies in Semarang. To fulfill this goal, the study was conducted on workers who were grouped by generation according to age or year of birth. To these respondents, employee engagement was measured which was then carried out a comparative test to determine the significance of differences in employee engagement in each generation. The results of the statistical tests carried out show that statistically it can be proven that workers from the Baby Boomer generation, X generation and Y generation have different employee engagement